If at First You Don’t Succeed: The Effect of the Option to Resolicit on Corporate Takeovers - Gillette, Ann B.; Noe, Thomas H. (Review of Financial Studies, 2006)
This article models, and experimentally simulates, the free-rider problem in a takeover when the raider has the option to “resolicit,” that is, to make a new offer after an offer has been rejected. In theory, the option to resolicit, by lowering offer credibility, increases the dissipative losses associated with free riding. The outcomes of our experiment support this prediction and produce losses from free riding even higher than theoretically predicted. These dissipation losses reduce raider gains to less than 3% of synergy value of the acquisition